Effectiveness of Percutaneous Electrolysis in Supraspinatus Tendinopathy: A Single-Blinded Randomized Controlled Trial. - Rodríguez-Huguet, Manuel; Góngora-Rodríguez, Jorge; Rodríguez-Huguet, Pablo; Ibáñez-Vera, Alfonso Javier; Rodríguez-Almagro, Daniel; Martín-Valero, Rocío; Díaz-Fernández, Ángeles; Lomas-Vega, Rafael (MPDI, 2020)
Supraspinatus tendinopathy is one of the most common causes of shoulder pain. Many studies support conservative treatments such as exercise, trigger point dry needling or corticosteroid injections. Otherwise, a minimally invasive approach with percutaneous electrolysis (PE) has also been used successfully in shoulder pain, although evidence about its long-term effects is scarce. The aim of this trial was to determine the effects of PE on supraspinatus tendinopathy compared with trigger point dry needling (TDN). Thirty-six patients with supraspinatus tendinopathy were randomly assigned to either a PE group (n = 18) or a TDN group (n = 18). Both groups also performed eccentric exercises. The main outcome to be measured was the Numerical Pain Rating Scale (NPRS), but the shoulder range of motion (ROM) and trigger point pressure pain threshold (PPT) were also considered. A one-year follow-up was conducted. Significant differences favoring the PE group were found regarding pain at one-year follow-up (p = 0.002). The improvement achieved in the PE group was greater in the NPRS (p < 0.001), proximal PPT, middle PPT, distal PPT (all p < 0.001) and ranges of movement. PE seems to be more effective than TDN in relieving pain and improving ROM and PPT supraspinatus values in patients with supraspinatus tendinopathy, both right after treatment and at one-year follow-up.
Keywords: Hombros - Lesiones y heridas; Fisioterapia; supraspinatus tendinopathy; Percutaneous electrolysis; Trigger point dry needling; Shoulder pain